Politiques publiques et élevage en Uruguay : premiers effets des mesures environnementales et de développement territorial - Éric Sabourin; Maria Fernanda de Torres Álvarez; Pedro Arbeletche; Gilles Massardier; Virgina Courdin; Jean François Tourrand; Hermes Morales Grosskopf (VertigO)
Recent public policies in favor of family farming in Uruguay face a lot of tension with the dominant neoliberal logic of Uruguayan agriculture. This paper analyzes the public policy innovations in the management of natural resources, land use and rural development decentralization. It also examines their effects, especially on the area of family livestock farming. The research was conducted by crossing archives analysis and interviews with key decision makers, stakeholders and beneficiaries of the studied policies. Uruguay is in the process of integrating international standards in environmental policies (conservation of water and soil) and regional sustainable development. But the implementation of new regulatory instruments (territorial, environmental, land use, etc.) has problems as they come in tension or conflict with the interests of the corporate sector or with the identity of livestock family farmers.